2015
DOI: 10.1159/000441576
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Biocompatibility of Dialysis Membranes

Abstract: Background: Improvements in the biocompatibility of dialysis membranes have reduced biological responses elicited by blood-membrane interactions. In this article, recent technological developments in dialysis membranes with regard to biocompatibility and recent progress in the evaluation of the biocompatibility of dialysis membranes are reviewed. Summary: The focus of investigation into dialysis membranes in recent years has focused on not only membrane materials, but also their surface textures, which have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 22 publications
3
51
0
2
Order By: Relevance
“…Biocompatibility testing is of utmost importance before approval of such devices for commercial use [38]. As described by Kokubo et al [39], experimental studies to test for membranes biocompatibility (sorbent material in the case of adsorption) can be performed using porcine blood/platelet-rich plasma (with leukocytes), looking for signs of platelet activation. It can also be done using suspension of neutrophils isolated from porcine blood looking for production of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…Biocompatibility testing is of utmost importance before approval of such devices for commercial use [38]. As described by Kokubo et al [39], experimental studies to test for membranes biocompatibility (sorbent material in the case of adsorption) can be performed using porcine blood/platelet-rich plasma (with leukocytes), looking for signs of platelet activation. It can also be done using suspension of neutrophils isolated from porcine blood looking for production of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…Here we have shown that modifications to the CTA material, primarily the smoother blood‐contacting surface, have given ATA membrane an improved biocompatibility profile vis‐à‐vis conventional CTA membrane, the latter being per se characterized by low protein adsorption properties ensuring good biocompatibility . Our results also indicate the usefulness of bioinformatics coupled to proteomic analyses in characterizing the biological reactions which may be elicited by activated surface‐adsorbed proteins.…”
Section: Discussionmentioning
confidence: 60%
“…The material of the dialysis membrane is the main determinant of the biological responses occurring during the HD procedure. Thus, modification of surface material designed to optimize both the chemical and the physical properties of blood‐exposed membrane surface, is essential in order to improve biocompatibility …”
Section: Discussionmentioning
confidence: 99%
“…Smoothers membrane have lesser platelets adhesion and BSA adsorption. 20 Increase POC content reduce membrane surface roughness as shown in Figure 3, hence would lead to lower platelet adhesion and protein adsorption, thus improve membrane hemocompatibility.…”
Section: Discussionmentioning
confidence: 99%